Antioxidant Potential of Indian Gooseberry (Emblica officinalis) Paste in Chicken Meatballs - Abinayaselvi, R.; Santhi, D.; Kalaikannan, A.; Natarajan, A.; Nandhini, K. (Journal of Meat Science, 2022)
The aim of the study was to evaluate the antioxidant potential of Indian gooseberry (Emblica officinalis) paste in chicken meatballs and its effect on physicochemical and sensory properties. Chicken meatballs were prepared with the inclusion of Indian gooseberry paste (GBP) at 0, 12%, 15%, and 18% levels. The emulsion pH, product pH, emulsion stability, and product yield were determined. DPPH Scavenging Activity (%) was studied to establish the antioxidant potential of the GBP in the product. Sensory properties were evaluated using 8 points hedonic scale.  Emulsion pH and Product pH decreased significantly (P
Keywords: Antioxidant activity; Chicken meatballs; Emblica officinalis; Physicochemical quality; Sensory properties